Development and Evaluation of an AI-based Exergame Training System for Ice-Hockey Players: a Randomized Controlled Trial - Nicole Sieber; Simon Walser; Thomas Weber; Raphael Gubler; Hannes Badertscher; Patrick Eggenberger (Current Issues in Sport Science (CISS), 2025)
Introduction: Executive functions (EF) are crucial for team sports athletes to perform effectively on the field. Especially in open-skill sports, such as ice-hockey, soccer, or volleyball, adaptability and responding appropriately to rapidly changing external cues are critical (Koch & Krenn, 2021). EF are divided into the three core components cognitive flexibility, inhibition or interference control, and working memory (Diamond, 2013). Elite athletes perform better in EF tasks compared to non-elite athletes (Logan et al., 2023) and higher EF may predict future elite potential in young team sports athletes (Lundgren et al., 2016; Vestberg et al., 2012). Exergaming combines exercise and video gaming and couples cognitive and physical stimuli. This innovative training approach was effective in improving cognitive functioning, particularly EF, in younger and older populations (Chan et al., 2024; Eng et al., 2023), however, has rarely been investigated in athletes (Martin-Niedecken et al., 2020). The main goal of this study was to develop a novel ice-hockey specific exergame and gain insights into its effects on EF in competitive ice-hockey players. Secondary outcomes included lower limb neuromuscular performance as well as exergame acceptance, usability, feasibility (adherence), and training intensity. Increased EF and neuromuscular performance in the intervention group were hypothesized. Methods: We developed the novel exergame training system using four synchronized cameras for video-based motion tracking of the athlete, in combination with two video projectors showing the game tasks on a wall-mounted screen and on the floor in front of the athlete. Artificial intelligence (i.e., machine learning) was applied to train and validate algorithms to accurately detect joint positions of the human body based on large open-source training and validation data sets. The exergame consists of cognitive tasks, including memorizing and catching or omitting various color-coded projected targets (e.g., circles, triangles, etc.), with either the left or right foot or hand. Simultaneously, various physical tasks, such as foot tapping, squats, lateral skating jumps, and single-leg jumps, must be performed at the highest possible frequency to imitate physical load during ice-hockey match play. To evaluate our novel exergame, 36 ice-hockey players from three male elite level teams (National League, U20, U17) and one female team (Swiss Women’s Hockey League B) of the SC Rapperswil-Jona Lakers participated. Half of each team’s players were randomly assigned to either the exergame intervention (n=18, female n=5, mean age 20.6 ± 5.0 years) or control group (n=18, female n=5, mean age 20.0 ± 5.8 years). While the control group followed the regular team training, the intervention group additionally trained twice weekly over five weeks with the novel exergame for 11 min per session (i.e., 3 x 3 min with 1 min rest). Pre- and post-intervention tests comprised two computerized neuropsychological EF tests (Victoria Stroop Test and Switcher Task, PEBL software) and the countermovement jump test (CMJ) on a force plate (Forcedecks, VALD Performance, Brisbane, Australia). Acceptance was assessed with the Exergame Enjoyment Questionnaire (EEQ, 20–100 points scale), usability was assessed with the System Usability Scale (SUS), and exergame training intensity was measured as percentage of maximum heart rate (%HRmax) and rating of perceived exertion (RPE, modified Borg scale 1–10). Two-way repeated measures analyses of variance (ANOVA) were used to analyze group x time interaction effects for EF and CMJ parameters. Results: In the Switcher Task, which reflects cognitive flexibility and working memory, a statistically significant medium sized effect, in favor of the exergame intervention group, was found for the time x group interaction in test condition 1 (F(1,34)=2.96, p=0.047 one-tailed, r=0.283) and a non-significant, but medium effect in test condition 3 (F(1,34)=2.65,p=0.057 one-tailed, r=0.269). The three Victoria Stroop Test conditions showed no significant or meaningful time x group interaction effects (p≥0.05). For the relative CMJ peak power [W/kg body weight], a statistically significant time x group interaction with medium effect size was evident (F(1,31)=3.10, p=0.044 one-tailed, r=0.301) and similarly, analyses showed a medium, however non-significant effect for CMJ jump height [cm] (F(1,31)=2.80, p=0.052 one-tailed, r=0.288). Exergame acceptance, usability, and adherence were very high, with 74.0 ± 8.5 points scored in the EEQ, 90.5 ± 9.8 points in the SUS, and an average of 9.7 ± 0.6 out of 10 training sessions performed, respectively. Objective and subjective exergame training intensities were high with 89.1 ± 7.8 %HRmax and RPE of 7.1 ± 1.1 points, respectively. Discussion/Conclusion: The 5-week training intervention with our newly developed exergame indicated positive effects on cognitive flexibility, working memory, and lower limb neuromuscular performance. Exergame intensity successfully mirrored the high-intensity characteristics of ice-hockey match play (Naimo et al., 2015) and may therefore have contributed to EF improvements (Ai et al., 2021). A longer intervention duration might further increase effects, however, was not possible due to the busy training and match schedule. Therefore, future research should explore the impact of the exergame on EF and physical performance over a longer period and in a larger number of players to substantiate the current findings. Several opportunities for improvements of the game scenario, cognitive challenge, and difficulty progression were identified and could lead to higher cognitive training load and effects on EF. In conclusion, the exergame’s purpose of an effective and enjoyable training tool was supported by the study, indicating its potential for long-term integration into off-ice training programs of competitive ice-hockey players. References Ai, J.-Y., Chen, F.-T., Hsieh, S.-S., Kao, S.-C., Chen, A.-G., Hung, T.-M., & Chang, Y.-K. (2021). The effect of acute high-intensity interval training on executive function: A systematic review. International Journal of Environmental Research and Public Health, 18(7), 3593. https://www.mdpi.com/1660-4601/18/7/3593 Chan, J. Y. C., Liu, J., Chan, A. T. C., & Tsoi, K. K. F. (2024). Exergaming and cognitive functions in people with mild cognitive impairment and dementia: A meta-analysis. npj Digital Medicine, 7(1), 154. https://doi.org/10.1038/s41746-024-01142-4 Diamond, A. (2013). Executive functions. Annual Review of Psychology, 64, 135–168. https://doi.org/10.1146/annurev-psych-113011-143750 Eng, C. M., Flynn, R. M., Thiessen, E. D., & Fisher, A. V. (2023). A literature review on the effects of exergames on executive function in youth. Technology Mind and Behavior, 4(3). https://doi.org/10.1037/tmb0000118 Koch, P., & Krenn, B. (2021). Executive functions in elite athletes – Comparing open-skill and closed-skill sports and considering the role of athletes' past involvement in both sport categories. Psychology of Sport and Exercise, 55, 101925. https://doi.org/10.1016/j.psychsport.2021.101925 Logan, N. E., Henry, D. A., Hillman, C. H., & Kramer, A. F. (2023). Trained athletes and cognitive function: A systematic review and meta-analysis. International Journal of Sport and Exercise Psychology, 21(4), 725–749. https://doi.org/10.1080/1612197X.2022.2084764 Lundgren, T., Högman, L., Näslund, M., & Parling, T. (2016). Preliminary investigation of executive functions in elite ice hockey players. Journal of Clinical Sport Psychology, 10(4), 324–335. https://doi.org/10.1123/jcsp.2015-0030 Martin-Niedecken, A. L., Mahrer, A., Rogers, K., de Bruin, E. D., & Schättin, A. (2020). “HIIT” the ExerCube: Comparing the effectiveness of functional high-intensity interval training in conventional vs. exergame-based training. Frontiers in Computer Science, 2. https://doi.org/10.3389/fcomp.2020.00033 Naimo, M. A., de Souza, E. O., Wilson, J. M., Carpenter, A. L., Gilchrist, P., Lowery, R. P., Averbuch, B., White, T. M., & Joy, J. (2015). High-intensity interval training has positive effects on performance in ice hockey players. International Journal of Sports Medicine, 36(1), 61–66. https://doi.org/10.1055/s-0034-1382054 Vestberg, T., Gustafson, R., Maurex, L., Ingvar, M., & Petrovic, P. (2012). Executive functions predict the success of top-soccer players. PLoS ONE, 7(4), e34731. https://doi.org/10.1371/journal.pone.0034731